ҚАЗАҚСТАН РЕСПУБЛИКАСЫНЫҢ АЗАМАТТАРЫНЫҢ ТУРИСТІК ҚАЛАУЛАРЫ: ЕРЕКШЕЛІГІ ЖӘНЕ СИПАТЫ (Journal of Economic Research & Business Administration, 2015)
In given article the materials, concerning developments of tourist business of Republic Kazakhstan, and also development of internal tourist business in our country are considered. Statistics about preferences of tourists of ourcountry that is where exactly the domestic tourist prefers to go to have a rest are given. Comparison between domestic and foreign vacation spot is resulted.